Change and development in organisations : towards consciousness, humanity and innovation - Chiva, Ricardo (New York, NY : Routledge, 2021)
"Due to the increasing transformation and changes in the economy, society, technology, ecology or even human health, organizations and companies are or should be continuously changing in order to survive as they are open systems. This book illustrates both how organizations can transform or change and where the most cutting-edge and innovative organizations and companies are heading. Accordingly, the book is structured in two parts. The first part explores concepts associated with change and development such as innovation, organisational resilience and learning, and describes the latest trends and related research. The second part analyses the new organisation or company we are, it is to be hoped, heading for: a more conscious, compassionate, sustainable, innovative, trustful and humane organisation. The book reviews underlying ideas related to leadership, technology, trust and compassion and presents and analyses compassionate, sustainable and conscious organisations through an in-depth examination of their organisational and managerial characteristics, with particular emphasis on their human resource management practices and employee wellbeing. This volume is principally addressed to management and business students and researchers, as it offers a pedagogical review and analysis of the topics from the latest literature and research. At the same time, it provides highly topical and interesting ways forward for executives who want to transform their companies by introducing more conscious, humane and innovative approaches"--
OCLC-licensed vendor bibliographic record.
Keywords: Organizational change; Strategic planning; Personnel management; Leadership; BUSINESS & ECONOMICS / Organizational Behavior; BUSINESS & ECONOMICS / Management